Efficacy and safety of subcutaneous injection of botulinum toxin in the treatment of Chinese postherpetic neuralgia compared to analgesics: a systematic review of randomized controlled trials and meta-analysis - Wang, Hui; Lin, Ping (Frontiers in Neurology, 2024)
Objective The purpose of this meta-analysis is to investigate the efficacy and safety of a subcutaneous injection of botulinum toxin in the treatment of postherpetic neuralgia (PHN) compared to analgesics. Methods We searched PubMed, Cochrane Library, Embase, Web of Science, Chinese National Knowledge Infrastructure (CNKI), and Wanfang for randomized controlled trials (RCTs) from inception to 10 September 2023. The primary clinical outcomes included visual analog scale (VAS) pain scores and clinical effective rates. The secondary clinical outcome included the adverse event rate during follow-up. Results A total of 14 studies with 1,358 participants were included in the meta-analysis. Among the included patients, 670 participants received botulinum toxin A injections and 688 participants received other medication treatments. The botulinum toxin-A (BTX-A) group exhibited lower pain scores [week 2: Mean difference (MD): −1.91, 95% confidence interval (CI): −2.63 to −1.20, and p < 0.00001; week 4: MD: –1.69, 95% CI: −2.69 to −0.68, and p < 0.00001; week 8: MD: –1.66, 95% CI: −2.20 to −1.12, and p < 0.00001; week 12:MD: –1.83, 95% CI: −2.70 to −0.96, and p < 0.00001; and week 24: MD: -1.07, 95% CI: −1.16 to −0.99, and p < 0.00001]. The effective rate was significantly higher in patients who received BTX-A for postherpetic neuralgia compared to those who received lidocaine or gabapentin (lidocaine: MD: –1.55, 95% CI: −2.84 to −0.27, and p = 0.02 and gabapentin: MD: –1.57, 95% CI: −2.12 to −1.02; and p < 0.00001). There was no difference in the incidence of adverse events between the treatment groups [odds ratio (OR): 1.25, 95% CI: 0.43 to 3.61, and p = 0.69]. Conclusion Our meta-analysis showed that BTX-A has certain advantages in relieving postherpetic neuralgia compared to analgesics. In addition, BTX-A is safe for treating postherpetic neuralgia, with no notable side effects. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42021289813.